(3JMdjd CSS GdGOGQI GdYGeI (B:s (3efXhQ eYGUQ (B/s - (3GdgjJj, UdGM GdOjfs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2009)
(3GdEOGQI GdYGeI (B: (3Gdeaghe , GdhXGFa , GdCgOGa , GdEOGGQI GdYGeI aj GdESdGe , eONd OQGSI GdEOGQIGdYGeI GdJCSjSjI h GdJWhjQjI , GdJMdjd GdeYGUQ ddEOGQI GdYGeI , GdefXhQ GdCjchdhLj dHjFI GdEOGQI GdYGeI , EOGQI GdeYQaI h JcfhdhLjG GdeYdheGJ h GdMcheI GdEdcJQhfjI , GdJfXje GdEOGQj GdMchej , ebOeI aj UfY GdSjGSI GdYGeI, GdehGRfI GdYGeI ddOhdI , EOGQI GdehGQO GdHTQjI , GdEOGQI GdeMdjI `` GdMce GdeMdj (B.s
(3eQGLY U(B.300s
Keywords: (3EOGQI GdGYeGds; (3GdGOGQIs; (3GdGOGQI GdYGeIs; (3GdJfXje GdGOGQjs